If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4v-12=-2(v-2)
We move all terms to the left:
4v-12-(-2(v-2))=0
We calculate terms in parentheses: -(-2(v-2)), so:We get rid of parentheses
-2(v-2)
We multiply parentheses
-2v+4
Back to the equation:
-(-2v+4)
4v+2v-4-12=0
We add all the numbers together, and all the variables
6v-16=0
We move all terms containing v to the left, all other terms to the right
6v=16
v=16/6
v=2+2/3
| X-34=2x-12 | | X^2+(7x/9)^2=130 | | 6x+2=8x+9 | | -2(x-4)=-32 | | 5/2x+3/5=3/5 | | -12a-1=11a | | 4e=2e+16 | | 12x+54=-8x-4(-5x+2 | | -5q+2q=16 | | 2.5(6x-8)=0.3(9x+12) | | 6x+7=127 | | 46.50m+60.00=39.00m+75.00 | | (4-12x)6x÷5=0 | | 4^×=16.2^x | | -2/x=1 | | 3x4+4+2x=-15 | | 7.25d+5=6.25d+9 | | 7(n-1)=-2(2+n) | | -9v−8=-7v | | -9−5b=-6b | | 3x-4+4+2x=x15 | | 6+5w=3w | | 9+2x-4x=-9 | | 6+2.5n-0.5n=10 | | -2x-3=2x+5-x | | -10+x+5=10 | | 7t-52=3t | | 12-7x-10=x-8+2 | | -7x-10=x-8+2 | | 7p+1=8p-16 | | 10-x-1=7+3x+2 | | 81+9=x |